SINTESIS NANOMATERIAL MAGNETIT-SITRAT DAN PENGUJIAN APLIKASINYA SEBAGAI ADSORBEN EMAS (III) - Susanto Susanto; Ricka Prasdiantika; Theodor C.M. Bolle (Universitas Gadjah Mada, 2017)
This study aims to synthesize of magnetite nanomaterial was dispersed with trisodium citrate (Fe3O4@citrate), carry out the characterization, and testing of its application in adsorbing of Au(III). Research carried out by synthesis of Fe3O4 with stirring using ultrasonic waves to synthesis of magnetite in the system of co-precipitation, using sodium citrate as dispersing agent of magnetite, and using acetone-water as solvent at washing of magnetite. Synthesized product was characterized by Fourier Transform Infrared spectrophotometer (FTIR), X-ray diffractometer (XRD), and transmission electron microscope (TEM). The characterized results indicate that Fe3O4@citrate has successfully synthesized with particle size of 17 nm. Fe3O4@citrate has smaller particle size, has smaller aggregates and has better particle dispersion than Fe3O4 without citrate. Testing the potential of synthesized Fe3O4@citrate as adsorbent of Au(III) from HAuCl4 solution of 200 ppm at pH 3. The Synthesized Fe3O4@citrate adsorbed the gold(III) of (81.554 ± 1.403) mg/g.